Foreign Language Teacher Competences: A Systematic Review of Competency Frameworks - Aysel Deregözü (Ankara Üniversitesi Eğitim Bilimleri Fakültesi Dergisi)
The aim of this study is to determine competences needed in the language teaching profession. For this aim, six frameworks for language teacher competency are examined. Data is analysed by using content analysis method. The required skills and knowledge are categorized under the aspects learning, learner, teaching, assessment and evaluation, linguistic competences, language awareness, professional development, leadership, culture, school and environment, teaching experience and technology. The results revealed that linguistic and language teaching core competences are crucial competences for language teachers. Yet, the frameworks lay diverse focus on knowledge and skills related to these competences. Out of the results, it is evident that a common framework for language teachers is needed, as all frameworks seem to be insufficient to give a full overview regarding the required competences.